Investigation of Anti-Mycobacterial Activity of Orientin and Vitexin on the Six Mycobacterium tuberculosis Strains - Tülin Aşkun (European Journal of Biology)
Objective: Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis, which causes disease in all organs, 80% of which are in the lungs, and can sometimes spread to other organs. It can lead to death in untreated or inadequately treated patients. Treatment of tuberculosis is very difficult due to the resistance of mycobacteria to many chemicals and disinfectants, antibiotics, and chemotherapeutics, especially in immunocompromised patients (HIV, Human Immunodeficiency Virus); this disease is very common. Therefore, in recent years, the search for new drugs to be used to treat tuberculosis has increased worldwide. We aim to determine the effect of orientin and vitexin on M. tuberculosis strains.Materials and Methods: In this study, the effects of orientin and vitexin against M. tuberculosis standard strains (M. tuberculosis H37Ra and M. tuberculosis H37Rv) and six-clinical M. tuberculosis strains. The inoculum was prepared using a positive BACTEC“Mycobacteria Growth Indicator Tube” containing 7H9 Broth. Microplate Presto Blue Method and rifampicin were used as standard antibiotics in the anti-mycobacterial assay.Results: Orientin and vitexin showed a mycobactericidal effect on tuberculosis strains depending on the concentration. Orientin and vitexin have not been tested on current clinical strains of M. tuberculosis before. In this respect, it is the first report describing the anti-mycobacterial activity of both orientin and vitexin.Conclusion: These results indicate that orientin and vitexin may be helpful for further investigations into their role in inhibitingM. tuberculosis. They have a possibility of new anti- mycobacterial drug candidates in the near future.